Allelopathic effects of native and invasive Brassica nigra do not support the novel‐weapons hypothesis. Issue 8 (7th August 2020) - Oduor, Ayub M. O.; van Kleunen, Mark; Stift, Marc
Abstract : Premise: The novel‐weapons hypothesis predicts that some plants are successful invaders because they release allelopathic compounds that are highly suppressive to naïve competitors in invaded ranges but are relatively ineffective against competitors in the native range. For its part, the evolution of enhanced weaponry hypothesis predicts that invasive populations may evolve increased expression of the allelopathic compounds. However, these predictions have rarely been tested empirically. Methods: Here, we made aqueous extracts of roots and shoots of invasive (North American) and native (European) Brassica nigra plants. Seeds of nine species from North America and nine species from Europe were exposed to these extracts. As control solutions, we used pure distilled water and distilled water with the osmotic potential adjusted with polyethylene glycol (PEG) to match that of root and shoot extracts of B. nigra . Results: The extracts had a strong negative effect on germination rates and seedling root lengths of target species compared to the water‐control. Compared to the osmolality‐adjusted controls, the extracts had a negative effect on seedling root length. We found no differences between the effects of B. nigra plant extracts from the invasive vs. native populations on germination rates and seedling root growth of target plant species. Responses were largely independent of whether the target plant species were from the invaded or native range of B. nigra . Conclusions: The results show that B. nigra can interfere with other species through allelochemical interactions, but do not support predictions of the novel‐weapons hypothesis and evolution of increased allelopathy.